Mapping the transition to superwetting state for nanotextured surfaces templated from block-copolymer self-assembly. Issue 44 (5th November 2018) - Telecka, Agnieszka; Mandsberg, Nikolaj Kofoed; Li, Tao; Ludvigsen, Emil; Ndoni, Sokol; Di Mundo, Rosa; Palumbo, Fabio; Fiutowski, Jacek; Chiriaev, Serguei; Taboryski, Rafael
Abstract : The transition to superwetting of hydrophilic nano-textured surfaces is mapped in terms of surface chemistry and texture geometry. Abstract : Adding roughness to hydrophilic surfaces is generally expected to enhance their wetting by water. Indeed, global free energy minimization predicts decreasing contact angles when roughness factor or surface energy increases. However, experimentally it is often found that water spreading on rough surfaces is impeded by pinning effects originating from local free energy minima; an effect, largely neglected in scientific literature. Here, we utilize Laplace pressure as a proxy for these local minima, and we map the transition to a superwetting state of hydrophilic nano-textured surfaces in terms of surface chemistry and texture geometry. We demonstrate the effect for polymer model surfaces templated from block-copolymer self-assembly comprising dense, nano-pillar arrays exhibiting strong pinning in their pristine state. By timed argon plasma exposure, we tune surface chemistry to map the transition into the superwetting state of low contact angle, which we show coincide with the surface supporting hemiwicking flow. For the near-ideal model surfaces, the transition to the superwetting state occurs below a critical material contact angle of ∼50°. We show that superwetting surfaces possess anti-fogging properties, and demonstrate long term stability of the superwetting effect by coating the nanotextured surfaces with ∼10 nm thin films of either tungsten or silica.